Survei Penilaian Mahasiswa pada Penentuan Sistem Pembelajaran Terbaik Setelah Pembelajaran Online Selama Covid 19 - Nailis Sa'adah; Taufik Hidayat (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2022)
The Covid-19 pandemic began to hit Indonesia since 2020. As a result of the pandemic, almost all aspects and areas of life have been affected. One of them is in the field of education. The government enforces online learning for all levels of education, including universities. There are many differences that are felt by students when participating in online learning. This study aims to determine student assessments in deciding the best learning system after online learning was implemented during the COVID-19 pandemic based on learning quality criteria and learning outcomes. The survey involved 43 student respondents. The research was conducted by applying the descriptive method. Data analysis of survey results was carried out using the Analytic Hierarchy Process (AHP) method. The results showed that the learning outcomes criteria had a higher weight, namely 36.92% compared to the learning quality criteria of 33.86% with a consistency ratio of <10% so that they had a good consistent level. The best alternative learning system is the offline learning system which has a weight of 66.42% while the online learning system has a weight of 33.58%. Overall, the AHP method succeeded in producing a fairly good consistency score in determining the best learning system based on the data from the student assessment survey.